Long non‐coding RNA MALAT1 regulates retinal neurodegeneration through CREB signaling - Jin Yao; Xiao‐Qun Wang; Yu‐Jie Li; Kun Shan; Hong Yang; Yang‐Ning‐Zhi Wang; Mu‐Di Yao; Chang Liu; Xiu‐Miao Li; Yi Shen; Jing‐Yu Liu; Hong Cheng; et al. (EMBO Molecular Medicine)
Abstract The nervous and vascular systems, although functionally different, share many common regulators of function maintenance. Long non‐coding RNAs (lncRNAs) are important players in many biological processes and human disorders. We previously identified a role of MALAT1 in microvascular dysfunction. However, its role in neurodegeneration is still unknown. Here, we used the eye as the model to investigate the role of MALAT1 in retinal neurodegeneration. We show that MALAT1 expression is significantly up‐regulated in the retinas, Müller cells, and primary retinal ganglion cells (RGCs) upon stress. MALAT1 knockdown reduces reactive gliosis, Müller cell activation, and RGC survival in vivo and in vitro. MALAT1‐CREB binding maintains CREB phosphorylation by inhibiting PP2A‐mediated dephosphorylation, which leads to continuous CREB signaling activation. Clinical and animal experimentation suggests that MALAT1 dysfunction is implicated in neurodegenerative processes and several human disorders. Collectively, this study reveals that MALAT1 might regulate the development of retinal neurodegeneration through CREB signaling.